THE RELATIONSHIP BETWEEN PERSONAL HYGIENE AND THE INCIDENCE OF PITYRIASIS VERSICOLOR IN SUKAWINATAN LANDFILL SCAVENGERS - Cantika Brigitta; Susilawati; Dalilah; Gita Dwi Prasasty; Dwi Handayani (Jurnal Kedokteran dan Kesehatan : Publikasi Ilmiah Fakultas Kedokteran Universitas Sriwijaya, 2026)
Pityriasis versicolor is a superficial fungal skin disease and a global health concern. Scavengers working under the scorching sun with behaviors such as not showering immediately after work, rarely changing work clothes, and using damp towels are at an increased risk of developing P. versicolor. This study aimed to determine the relationship between personal hygiene and the occurrence of P. versicolor among scavengers at the Sukawinatan landfill. The research employed an analytical observational method with a cross-sectional design and total sampling technique. Forty-eight scavengers who met the inclusion and exclusion criteria were included as study subjects. Personal hygiene data were collected through questionnaires, while data on P. versicolor were obtained from clinical symptoms and examinations using a Wood's lamp. The results showed that 22.9% of the scavengers at the Sukawinatan landfill had P. versicolor. Fisher's Exact test revealed a significant relationship between personal hygiene and the occurrence of P. versicolor, with a p-value of 0.002 (p < 0.05) and a Prevalence Ratio (PR) of 5.200 (PR > 1.000). In conclusion, there is a significant relationship between personal hygiene and the occurrence of Pityriasis versicolor among scavengers at the Sukawinatan landfill.